Evaluation of Technology Commercialization Factors in Kazakhstan - G. Zh. Alibekova; B. M. Yedgenov; A. K. Kozhakhmetova; E. N. Mynbaeva (Экономика: стратегия и практика, 2024)
The commercialization of scientific research and development (R&D) results is a key driver for enhancing corporate revenues and profits, positively impacting economic development, and increasing global and national competitiveness. However, commercialization is a complex process influenced by various factors. This study aims to assess the mutual influence of commercialization factors of R&D in Kazakhstan and provide recommendations to strengthen positive influences and mitigate negative ones. Utilizing official data from the Bureau of National Statistics, including metrics such as enterprise innovation activity, the share of innovative products in GDP, patent numbers, R&D expenditures, industry innovation costs, and R&D personnel, a regression analysis was conducted using the time series method and the vector autoregression (VAR) approach. The analysis revealed that increased innovative activity of enterprises positively impacts the export of innovative products after three years but negatively affects the share of innovative products in GDP. Additionally, higher industry innovation costs and an increase in patent numbers lead to a rise in innovative product exports after three years. However, an increase in innovative product exports subsequently reduces patent numbers after three years. These results indicate that domestic enterprises focus primarily on expanding export-oriented products for short-term profit gains, reducing costs, and achieving immediate results, often at the expense of substantial innovation activities. The findings suggest a need for strategies to balance short-term profit motives with sustainable innovation investments to enhance long-term economic growth and competitiveness.